Problemy agencji w przedsiębiorstwach rodzinnych - perspektywy badawcze - Lizińska, Joanna (Agency Problems in Family Firms -Exploratory Challenges, 2008)
Agency theory would predict a low level of agency costs within family firms because of the fusion of ownership and control. However, many studies challenges this oversimplification and new questions rise whether agency costs are really mitigated. Family members are expected to be altruistic toward each other, which can either increase or decrease performance. Stewardship theory is an alternative perspective to explore family involvement in a business. Another set of questions concerns the agency costs of debt in family-controlled businesses. This is because of the look at the conflict of interests between shareholders and bondholders. The last but not least, a problem of expropriation of minority stockholders rises. It appears especially when a family controls a group of companies. The exploratory results suggest that agency problems in family firms are more complicated than expected as new research perspectives are introduced.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 367-374